Pars plana vitrectomy in patients with myopic macular retinoschisis. Issue 4 (10th January 2014) - Chang, Jonathan S; Flynn, Harry W; Engelbert, Michael; Shane, Anita R; Smiddy, William E; Chang, Stanley
Abstract : Background/aims: To report the outcomes of patients undergoing pars plana vitrectomy (PPV) for myopic macular retinoschisis. Methods: Retrospective, non-randomised case series of patients who underwent PPV for myopic macular retinoschisis. Macular holes and foveal retinal detachments that occurred with myopic macular retinoschisis were also included in the series. Myopic macular retinoschisis was confirmed with optical coherence tomography. Visual acuity (VA) and central foveal thickness (CFT) were measured at baseline and 6 months following surgery. Results: A total of 41 eyes were identified that met the inclusion criteria. The mean follow-up time was 192 days (range 132–272). The mean preoperative VA was 20/130, and the mean VA at 6 months was 20/70 (p=0.02). Following surgery, 14 (34.1%) eyes had VA of 20/40 or better. In 15 (36.6%) eyes, VA was 20/50–20/100 and in 12 (29.2%) eyes, VA was 20/200 or worse. CFT improved from a mean of 558 microns at baseline to 265 microns at 6 months (p<0.001). Conclusions: PPV generally resulted in stable or improved VA for eyes with myopic macular retinoschisis. Eyes with concurrent macular hole or foveal retinal detachment often had improved VA, but to a lesser extent than eyes with myopic macular retinoschisis alone.